Strategi Pembelajaran Orangtua Dalam Melaksanakan Homeschooling Untuk Anak - Ariyani, Yuli; , Dr. Sri Lestari, M.Si s; , Dr. Moordiningsih, M.Si, Psi (2016)
The research aims to describe the phenomenon in learning strategy which is applied by homeschooler parents (father and mother). This research uses a qualitative method and takes the form of phenomenology. The collecting data by interview. Analysis of this data uses interactive analysis techniques, there are data collection, data reduction, data presentation, and conclusion or verification. haracteristics of the informant is homeschooling parents who run single homeschooling with teen age junior high and senior high school children. Informants are 4 families consists of four mothers, four fathers, and four children. The data collection method uses an interview. Results of the research: 1) The learning strategies are applied by parents in homeschooling are child centered learning (indirect instruction), nteractive instruction, Experiential learning, independent study. mother applies quantum teaching method while father applies reward punishment method; 2) The supporting factors in implementing homeschooling learning strategies are motivation and children responsibility and support facility; 3) The inhibiting factors in implementing homeschooling learning strategies are adolescence is still unstable, associated with schedule adjustments between parent and child, time division parent, learning demands of parents, parents should be a role model; 4) The impacts of homeschooling are its potential to grow, the child is not easy to stress, responsibility and independence in child; 5) Parents problem solving strategies in overcoming obstacles in carrying out homeschooling learning are motivation and gives examples of success stories of people around, comforting the child at home; 6) The motivation of parents choose homeschooling because of the fears of parents toward promiscuity, the formal school curriculum which is often mutually exchange; 7) Parents hope in carrying out homeschooling for children so that the potential of the child can develop optimally, the child is not affected promiscuity, children can be independent, learn to manage time, responsibility and also have the good moral;